2020
DOI: 10.1038/s43246-020-00090-2
|View full text |Cite
|
Sign up to set email alerts
|

Time limited self-organised criticality in the high rate deformation of face centred cubic metals

Abstract: Plastic deformation is a fundamentally important physical process, ultimately determining how materials can be used. Metal plasticity is governed by dislocation dynamics and lattice twinning. Although many continuum constitutive models exist, plasticity is now known to occur in discrete events arising from the self-organisation of dislocations into ‘avalanches’ under applied stress. Here we extend avalanche plasticity to high strain rates, by introducing time limitation to self-organisation. At high rates larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 60 publications
1
9
0
Order By: Relevance
“…Fig. 1 A compilation [6,12,16] of copper conventional and split Hopkinson pressure bar measurements leading at higher pressures to two stress dependencies [15,17] proposed to be applicable for shock-induced strength behaviors.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fig. 1 A compilation [6,12,16] of copper conventional and split Hopkinson pressure bar measurements leading at higher pressures to two stress dependencies [15,17] proposed to be applicable for shock-induced strength behaviors.…”
Section: Methodsmentioning
confidence: 99%
“…Figure 1 illustrates the behavioral transition for very recently reported [16] split Hopkinson pressure bar (SHPB) measurements made on copper material, with and without stress interruption, in comparison with a previous compilation [6,12] of conventional, SHPB, and shock results. The lower, approximately linear, stress dependencies, at two strain values, apply for Eq.…”
Section: Introductionmentioning
confidence: 94%
“…Figure 1 provides a compilation of SHPB and shock measurements based on the recent work of Lea et al [2] and including the previous Follansbee et al and dislocation mechanics descriptions of high-rate deformations [6]. The open-diamond and filled-circle measurements from Lea et al also include open-circle measurements made afterwards at the indicated strain rates to demonstrate that the strain hardening had been largely retained, as normally occurs for "shock hardening".…”
Section: The Dislocation Mechanics Of Rate-dependent Deformationmentioning
confidence: 99%
“…The open-diamond and filled-circle measurements from Lea et al also include open-circle measurements made afterwards at the indicated strain rates to demonstrate that the strain hardening had been largely retained, as normally occurs for "shock hardening". The approximately linear-fitted lower strain rate Lea et al and Follansbee et al measurements, in the latter case made at a compressive strain, ε = 0.15, are matched in the figure in each case with the face-centered cubic (fcc) form of the Z-A relationship for the flow stress, σ ε , that is expressed as [7] σ ε = σ Gε + B 0 [ε r (1 [1], ε = 0.15, SHPB measurements fitted to a Z-A relationship [7] and follow-on ε = 0.10 measurements reported by Lea et al [2], also shown in relation to extrapolation to the lower stress regime of experimental Swegle and Grady [5] and dislocation mechanics-based shock [4] descriptions.…”
Section: The Dislocation Mechanics Of Rate-dependent Deformationmentioning
confidence: 99%
See 1 more Smart Citation